A One-Pot Diastereoselective Synthesis of 2-[Aryl(hydroxy)methyl]-6-methyl-2H-furo[3,2-c]pyran-3,4-diones: Crystallographic Evidence for the Furanone Ring Closure - Abdi, Yamina; Boutemeur-Kheddis, Baya; Hamdi, Maamar; Talhi, Oualid; Paz, Filipe A. Almeida; Kirsch, Gilbert; Silva, Artur M. S. (Synlett, 2015)
Novel furopyran-3,4-dione-fused heterocycles have been obtained by a one-pot reaction of α-brominated dehydroacetic acid and benzaldehydes under organobase conditions. The prepared 2-[aryl(hydroxy)methyl]-6-methyl-2H-furo[3,2-c]pyran-3,4-diones were fully characterized by 2D NMR spectroscopy and supported by single-crystal X-ray analysis to unequivocally prove the furan-3-one five-membered ring-closure mechanism instead of the dihydroflavanon-3-ol six-membered cyclization which has recently been proposed in the literature.
Keywords: furan-3-ones; pyran-2-ones; dehydroacetic acid; synthesis; organobase; 2D NMRspectroscopy; single-crystal X-ray diffraction